eIF5A has a function in the cotranslational translocation of proteins into the ER - Rossi, Danuza [UNESP]; Galvo, Fabio Carrilho [UNESP]; Bellato, Hermano Martins [UNESP]; Boldrin, Paulo E. G. [UNESP]; Andrews, Brenda J.; Valentini, Sandro Roberto [UNESP]; Zanelli, Cleslei Fernando [UNESP] (Springer, 2014)
The putative eukaryotic translation initiation factor 5A (eIF5A) is a highly conserved and essential protein present in all organisms except bacteria. To be activated, eIF5A requires the conversion of a specific residue of lysine into hypusine. This hypusine modification occurs posttranslationally in two enzymatic steps, and the polyamine spermidine is the substrate. Despite having an essential function in translation elongation, the critical role played by eIF5A remains unclear. In addition to demonstrating genetic interactions with translation factors, eIF5A mutants genetically interact with mutations in YPT1, which encodes an essential protein involved in endoplasmic reticulum (ER)-to-Golgi vesicle transport. In this study, we investigated the correlation between the function of eIF5A in translation and secretion in yeast. The results of in vivo translocation assays and genetic interaction analyses suggest a specific role for eIF5A in the cotranslational translocation of proteins into the ER, but not in the posttranslational pathway. Additionally, we observed that a block in eIF5A activation up-regulates stress-induced chaperones, which also occurs when SRP function is lost. Finally, loss of eIF5A function affects binding of the ribosome-nascent chain complex to SRP. These results link eIF5A function in translation with a role of SRP in the cell and may help explain the dual effects of eIF5A in differential and general translation.
Keywords: Translation elongation; Hypusine; eIF5A; Cotranslational translocation; Endoplasmic reticulum